Participatory Ergonomics Training in the Manufacturing Sector and Ergonomic Analysis Tools - St-Vincent, Marie; Lortie, Monique; Chicoine, Denise (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2001)
SummaryThis article discusses the importance of job analysis tools for training in the context of participatory ergonomic processes. It explains the major principles and challenges in the design of these tools for short-cycle repetitive tasks and for long-cycle varied tasks. The intervention framework is described and the proposed tools are presented and related to the literature. The participants’ difficulties with the tools developed in both contexts studied are summarized. The discussion suggests that these difficulties are partly related to the company context and raises questions about the data relevant for the evaluation of solutions in the case of non-repetitive tasks.